Waktu Vaksinasi Avian Influenza (AI) yang Tepat untuk Menghasilkan Respon Imunologis Protektif pada Ayam Ras Pedaging - Dwi Desmiyeni Putri; Agung Adi Candra; Zairiful Zairiful (Politeknik Negeri Lampung., 2012)
The research was conducted to study best timing of AI vaccination to give protective respons for broiler. The experiment were devided into five trials. Each trial consisted of twenty birds. Each group got AI vaccination in different timing. The first group were vaccinated AI at third day. The second group were vaccinated AI in the same time with ND vaccination at fifth day. The third group got AI vaccination at seventh day. The parameter was observed in this study antibody responses against Newcastle Disease virus and Avian Influenza virus. The result of this study indicated that the antibody titer of birds that was vaccinated AI at seventh day higher than birds that were vaccinated AI in third day and fifth day. Keywords: Avian Influenza, Vaccination